2008
DOI: 10.1590/s1415-52732008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre risco de disfagia e risco nutricional em idosos internados em hospital universitário de Brasília

Abstract: R E S U M O ObjetivosInvestigar a associação entre o grau de risco de disfagia e o risco nutricional dos pacientes idosos internados na clínica médica do Hospital Universitário de Brasília. MétodosEstudo transversal, analítico, original, observacional, não-controlado, com amostra de conveniência e estratificada..Foram aplicados a Mini Avaliação Nutricional e o questionário de risco de disfagia em 49 pacientes idosos nas primeiras 48 horas após admissão na clínica médica, em setembro de 2006. ResultadosA freqüê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
8
0
8
Order By: Relevance
“…At the same time, it must be attractive as a standard meal and nutritionally complete 20 .There was disagreement between the results of this study with those found in the literature with regard to the food consistency of choice for restore the patient's verbal communication involves the occlusion of tracheostomy tube 19,20 . Another extremely useful feature in enabling verbalization and optimize swallowing is the speaking valve 6 .…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…At the same time, it must be attractive as a standard meal and nutritionally complete 20 .There was disagreement between the results of this study with those found in the literature with regard to the food consistency of choice for restore the patient's verbal communication involves the occlusion of tracheostomy tube 19,20 . Another extremely useful feature in enabling verbalization and optimize swallowing is the speaking valve 6 .…”
mentioning
confidence: 66%
“…In a particular study, the unidirectional speaking valve significantly reduced the incidence and severity of aspiration watery fluid, probably by restoring the subglottic air pressure and laryngeal awareness 6,21 . However, in another study the incidence of aspiration was not affected by the occlusion of the tracheostomy tube and/or the use of the unidirectional speaking valve 20 . In this study, it was noted a small number of speech therapists using the speaking valve as a therapeutic resource, despite the numerous benefits cited in the literature.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…7 The prevalence of malnutrition in hospitals ranges from 19 to 80% in medical and surgical patients, with higher rates seen among elderly individuals. 8 Since the dawn of medicine, malnutrition has been recognized as a sign associated with cardiac insufficiency, particularly in its later stages. Varying degrees of protein-calorie depletion can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…A atuação fonoaudiológica em hospitais é relativamente recente no Brasil, principalmente no que diz respeito ao acompanhamento de pacientes internados, mostrando-se uma prática em expansão em vários serviços brasileiros, com aumento de pesquisas nessa área (Kunigk e Chehter, 2007; Padovani e Padovani et al, 2008;Maciel et al, 2008). No cenário internacional, a fonoaudiologia hospitalar é praticada desde os anos 50 (Knapp, 1952) e a disfagia orofaríngea vem sendo amplamente estudada pela comunidade científica dessa categoria desde a década de 1980 (Price et al, 1987;Logemann, 1988;Erlichman, 1989;ASHA, 1989).…”
Section: Apresentaçãounclassified